'Every single minute and hour is scrutinised': neoliberalism and Australian private mental health care. Issue 2 (1st November 2019) - Dawson, Lisa; River, Jo; McCloughen, Andrea; Buus, Niels
Abstract: There is little understanding of how recovery‐oriented approaches fit within contemporary mental healthcare systems, which emphasise biomedical approaches to care, increased efficiency and cost‐cutting. This article examines the established models of service delivery in a private, youth, mental health service and the impacts of the current system on staff. It explores whether the service is prepared or capable of adopting recovery‐oriented approaches to care. Qualitative interviews were undertaken with staff and thematically analysed to understand the everyday practices on the unit. Data suggest that economic efficiencies and biomedical dominance largely shaped how health care was organised and delivered, which was perceived by staff as inflexible to change. Additionally, findings suggest that market‐oriented principles associated with neoliberalism restricted the capacity of individuals to transform services in line with alternative models of care and lowered staff morale. These finding suggest that, while neoliberal ideologies and biomedical approaches remain dominant in organisations, there will be challenges to adopting alternative recovery‐oriented models of care and promoting healthcare systems that understand mental health issues in broader socio‐political contexts and can flexibly respond to the needs of service users.